2023
DOI: 10.1111/cdev.13930
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social status on children's merit‐based resource allocation: The potential explanation of expectation

Abstract: How 3‐ to 11‐year‐old children integrate recipients' merit and social status when allocating resources was examined in 2021 and 2022. Study 1 (Han Chinese, n = 309, 150 girls) showed that while children prioritized merit, they developed from favoring high‐status recipients to favoring low‐status recipients. Study 2 (n = 194, 98 girls) and Study 3 (n = 138, 68 girls) revealed that children held stereotypes about the relation between merit and social status which shifted with age from expecting high‐status peers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In previous studies, it has been found that children as young as 3 years tended to give a larger share of resources to the more hard-working person as opposed to the less hard-working person in a collaborative context (Baumard et al, 2012;Hamann et al, 2014). In addition, this merit-based allocation tendency remains stable even with the interference of social factors Xiao et al, 2019;Zhang et al, 2023). For instance, in group scenarios where resources were allocated between in-group and out-group members who exerted high or low merit, children consistently adhered to allocating more resources to the high-merit person and were influenced minimally, if at all, by group bias .…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies, it has been found that children as young as 3 years tended to give a larger share of resources to the more hard-working person as opposed to the less hard-working person in a collaborative context (Baumard et al, 2012;Hamann et al, 2014). In addition, this merit-based allocation tendency remains stable even with the interference of social factors Xiao et al, 2019;Zhang et al, 2023). For instance, in group scenarios where resources were allocated between in-group and out-group members who exerted high or low merit, children consistently adhered to allocating more resources to the high-merit person and were influenced minimally, if at all, by group bias .…”
Section: Introductionmentioning
confidence: 88%